The influence of color association strength and consistency on ease of processing of ambient lighting feedback. (September 2016) - Lu, Shengnan; Ham, Jaap; Midden, Cees
Abstract: Lighting feedback may use colors that through their associations help users to easily process feedback messages and adapt their behavior. Study 1 showed more ease of processing (of feedback messages) only for participants receiving strongly -associated lighting feedback, as their processing times were not increased by additional cognitive load. Also, lighting feedback that was strongly associated with the message had stronger persuasive effects on behavior. Study 2 tested the effects of consistency of color association with the message. For example, while normally green is associated with low energy consumption, the inconsistent feedback condition showed green colors indicating high energy consumption. Results showed that only the inconsistent version of strongly -associated lighting feedback slowed down the processing of feedback messages. Also, consistent feedback had stronger persuasive effects on behavior. These findings increase our understanding of the psychological mechanisms of ambient persuasive technology showing the important role of strong and consistent associations of ambient lighting. Highlights: The psychological mechanism behind the ease of processing of ambient persuasive technology is investigated. Strong and consistent color associations can help users easily processing feedback messages. Using colors with strong and consistent associations can increase the behavioral effects of ambient lighting feedback.